Which data are available in central registries on bladder cancer patients in the five Nordic countries. (4th March 2021) - Körner, Stefanie Korsgaard; Dreyer, Thomas; Haug, Erik Skaaheim; Jerlström, Tomas; Boström, Peter J.; Gudjonsson, Sigurdur; Jensen, Jørgen Bjerggaard
Abstract: Objective: The aim of this study was to give a collective overview on all available data sources on bladder cancer patients in the Nordic countries including the amount of detail and coverage. Methods: National representatives from five Nordic countries were asked to fill out a questionnaire on available information regarding bladder cancer patients from databases in their respective countries. Additional information was retrieved from descriptions of the relevant registries. Results: Non-muscle invasive bladder cancer : from all countries, information on stage and grade at transurethral resection of the bladder (TURB) could be retrieved. Details on procedures (TURB, instillation therapy, photodynamic diagnosis, and perioperative instillation) were varying within different databases. Muscle invasive bladder cancer : in all Nordic countries, detailed information on cystectomy patients could be retrieved but with variable registration of complications. Completeness of available information on oncological treatment (radiation, chemotherapy, and immunotherapy) were varying. Oncological outcome : Information on overall survival was available in all countries whereas recurrence-free survival and cancer-specific survival were available for some but not all patients depending on treatment modality. Conclusions: Despite limitations, we found that it was possible to retrieve detailed information on diagnostics, treatment, and outcome for most aspects of bladder cancer in the Nordic countries on a population based, non-selected patient cohort.